The Impact of Islamic Philanthropic Mechanisms on Poverty Alleviation and Economic Resilience in the Wake of Fuel Subsidy Removal in Nigeria - Usman Jibril Mikail; Adamu Abubakar Muhammad; Bala Babangida; Abdulkareem Ahmad Tijjani; Maryam Adam (IDRIS Darulfunun Institute, 2025)
-